What the bones say : Tasmanian aborigines, science and domination - Cove, John J. (Carleton University Press, 1995)
What the Bones Say is a thoroughly engaging history of one line of human science research and its consequences for the hapless and often helpless subject of study: the indigenous peoples of Tasmania. Research questions arising from skeletal remains were posed and pursued on the assumption that vanished forebears bore no relation to, nor had any intrinsic meaning for, aboriginal Tasmanians of today. The author finds these premises incorrect, exposing both the biases of research done for political ends, and documenting their galvanizing effect on indigenous status and land claims, ownership of skeletal remains, the political mobilization of Aboriginal interests, and native advocacy.